2020
DOI: 10.1002/vms3.299
|View full text |Cite
|
Sign up to set email alerts
|

African swine fever recovery in China

Abstract: African swine fever (ASF) is the number one killer of swine on pig farms and has caused significant harm to pig farming in China since its spread. In this study, we designed a variety of physicochemical factors to explore the biological characteristics of ASF, so as to guide farms to develop disinfection measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…Our study showed that sodium hypochlorite was more effective in breaking down DNA of ASFV making sodium hypochlorite more favorable to use by avoiding confusing positive DNA with infectious ASFV particles especially when evaluating the cleaning and disinfection outcome. This is also consistent with ndings of a recent report that sodium hypochlorite and chlorine work well in damaging ASFV DNA 1 . These characteristics of ASFV constitute the scienti c foundation or our method and vice versa, our results supported these ndings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed that sodium hypochlorite was more effective in breaking down DNA of ASFV making sodium hypochlorite more favorable to use by avoiding confusing positive DNA with infectious ASFV particles especially when evaluating the cleaning and disinfection outcome. This is also consistent with ndings of a recent report that sodium hypochlorite and chlorine work well in damaging ASFV DNA 1 . These characteristics of ASFV constitute the scienti c foundation or our method and vice versa, our results supported these ndings.…”
Section: Discussionsupporting
confidence: 93%
“…The rst outbreak of ASF in China was reported on 3rd August, 2018 1 . Without vaccine, the only available tool to prevent ASFV is the implementation of strict bio-security measures at regional and farm level.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, China’s pork export volume was 210,000 tons, a year-on-year decrease of 36.17%, which has tremendous consequences for international trade. In the face of strong and sustained demand, the available pork supply has subsequently declined, leading to a substantial increase in the price of pork sold on the domestic market, from 12.2 yuan per kg (February 2019) to 36.1 yuan per kg in February 2020 [ 22 ]. The outbreak of ASF caused a considerable loss of pig capacity in China, and the pig industry has suffered a devastating blow.…”
Section: Epidemic Situation Of Asf In Chinamentioning
confidence: 99%
“…The diversification of breeding modes, high feeding density and weak biosafety awareness of practitioners have aggravated the pressure on the prevention and control of ASF in China. Therefore, more attention should be paid to improving animal husbandry and raising biosecurity levels [ 22 , 38 ].…”
Section: Factors Of Asf Prevalence In Chinamentioning
confidence: 99%
“…Chinese researchers insist that the long-distance transport of live pigs is unavoidable because the pig-producing field is not distributed uniformly throughout China [ 45 ]. Some Asian countries, such as China and Vietnam, have highly complex pig/pork production systems [ 46 ]. Other countries also have complex pig value chains that affect the movement of pigs, the feed-supply system, and shipment to slaughterhouses.…”
Section: Change and Preparation Of Asf Outbreaks For The Futurementioning
confidence: 99%